2018
DOI: 10.1186/s42408-018-0006-8
|View full text |Cite
|
Sign up to set email alerts
|

Restoring historical fire regimes increases activity of endangered bats

Abstract: Background: Fire suppression has altered ecological communities globally. Prescribed fire regimes strive to restore function to these fire-dependent ecosystems by mimicking natural fire regimes. Although fire frequency is a widely acknowledged component of fire regimes, the importance of fire seasonality for biodiversity is less clear but appears to play a critical role for a variety of taxa, particularly in the North American Coastal Plain. In subtropical Florida, USA, fire historically occurred primarily at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 54 publications
(79 reference statements)
0
7
0
Order By: Relevance
“…Furthermore, these sites provide roost areas with minimal risk of fire. The use of fire as a habitat management tool is believed to positively impact a wide range of bat species in the southeastern United States [25,27,29,30]. Outside of the southeastern United States, bat response often has focused on the wildfire rather than prescribed fire impacts on foraging activity, bat community structure and loss of habitat [38,84,85].…”
Section: Plos Onementioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, these sites provide roost areas with minimal risk of fire. The use of fire as a habitat management tool is believed to positively impact a wide range of bat species in the southeastern United States [25,27,29,30]. Outside of the southeastern United States, bat response often has focused on the wildfire rather than prescribed fire impacts on foraging activity, bat community structure and loss of habitat [38,84,85].…”
Section: Plos Onementioning
confidence: 99%
“…Depending on the bat species and habitat type therein, bat response to fire management practices generally is neutral to positive in the southeastern United States [23][24][25][26]. Repeatedly burned stands, with reduced overstory clutter and stocking, have increased foraging activity, relative to unburned stands particularly among less maneuverable, larger-bodied bats, or generalist foragers [27][28][29]. This increased forging activity occurs even though arthropod prey biomass, such as Lepidopterans, may decrease temporarily following burning [30].…”
Section: Introductionmentioning
confidence: 99%
“…3 Examples of studies from various regions and fire types (wildfire and prescribed fire) that have directly examined the spatial (top) and temporal (bottom) components of the relationship between bats and fire for sites burned during the cool, dry season (January-March), activity is higher in sites burned at low frequencies than at moderate frequencies. As discussed below, the most effective burn schedules for managing bat foraging habitat in an area may be those that best mimic the historical fire regime, which in south Florida is the early wet season based on burn seasons prior to European colonization (Braun de Torrez et al 2018b). Starbuck et al (2015) also found a positive relationship between evening bat (Nycticeius humeralis) (Rafinesque) habitat use and frequency of prescribed fires but found neutral effects for all other species analyzed (Additional file 3).…”
Section: Bat Responses To Burned Versus Unburned Sitesmentioning
confidence: 99%
“…Prescribed fire seasons often do not coincide with the historical fire season due to operational considerations as well as concerns about the direct and indirect effects on wildlife (Knapp et al 2009). However, E. floridanus respond most favorably to prescribed fires conducted during the historical season which is April to June (early wet season) (Braun de Torrez et al 2018b). In the Cumberland Plateau of Tennessee, foraging activity of several species is greater in sites that are burned in the spring compared to the fall but amount of thinning is also a factor (Cox et al 2016).…”
Section: Effects Of Fire Parameters On Bats-burn Seasonmentioning
confidence: 99%
“…Prescribed fire programs, an important component of this national strategy, attempt to restore historical fire regimes while potentially reducing the risk of large, high-severity wildfires (Ryan et al 2013;Schultz et al 2019). Balancing the risk of fire to human health and safety with the necessary role that fire plays in many ecosystems (Braun de Torrez et al 2018;Wiesner et al 2019;Kramer et al 2021) requires improved data on contemporary fire history metrics. However, while national, fire-related datasets such as burned area (Hawbaker et al 2020a), wildfire risk to populations (Scott et al 2020), and divergence from historical fire regime (Blankenship et al 2021) datasets are all available, contemporary, national fire history metrics, or a series of measures that help characterise the contemporary fire regimes and time since last burn,…”
Section: Introductionmentioning
confidence: 99%